(untitled) (Al Dzahab, 2024)
Purpose: This research examines Islamic Ethics Work, Hedonic Values, and Attitudes toward the Intention to Establish Sustainable Entrepreneurship. Design/methodology/approach: The research method used is quantitative with a conclusive research design. The primary data used is obtained through a questionnaire distributed on the internet, with the criteria of Muslim students. A total of 210 respondents were gathered. This study employs the SEM-PLS data analysis model. Findings: The results show that Islamic Ethics Work has a positive direct influence on Attitude, while Hedonic Values do not directly impact Attitude. Furthermore, the Islamic Ethics Work variable does not directly impact the Intention to Establish Sustainable Entrepreneurship. In contrast, Attitude has a positive influence, and Hedonic Values have a negative influence. Islamic Ethics Work positively influences the Intention to Establish Sustainable Entrepreneurship through Attitude. Meanwhile, Hedonic Values have little impact on the Intention to Establish Sustainable Entrepreneurship through Attitude. Research implications: The results of this study can have implications for developing entrepreneurship courses in higher education by incorporating Islamic Ethics Work to provide opportunities for students to adopt a sustainable entrepreneurship approach and reduce hedonism.